Oxycodone decreases anxiety-like behavior in the elevated plus-maze test in male and female rats. Issue 6 (3rd August 2022) - Bruijnzeel, Adriaan W.; Behnood-Rod, Azin; Malphurs, Wendi; Chellian, Ranjithkumar; Caudle, Robert M.; Febo, Marcelo; Setlow, Barry; Neubert, John K.
Abstract : The prescription opioid oxycodone is widely used for the treatment of pain in humans. Oxycodone misuse is more common among people with an anxiety disorder than those without one. Therefore, oxycodone might be misused for its anxiolytic properties. We investigated if oxycodone affects anxiety-like behavior in adult male and female rats. The rats were treated with oxycodone (0.178, 0.32, 0.56, or 1 mg/kg), and anxiety-like behavior was investigated in the elevated plus-maze test. Immediately after the elevated plus-maze test, a small open field test was conducted to determine the effects of oxycodone on locomotor activity. In the elevated plus-maze test, oxycodone increased the percentage of time spent on the open arms, the percentage of open arm entries, time on the open arms, open arm entries, and the distance traveled. The males treated with vehicle had a lower percentage of open arm entries than the females treated with vehicle, and oxycodone treatment led to a greater increase in the percentage of open arm entries in the males than females. Furthermore, the females spent more time on the open arms, made more open arm entries, spent less time in the closed arms, and traveled a greater distance than the males. In the small open field test, treatment with oxycodone did not affect locomotor activity or rearing. Sex differences were observed; the females traveled a greater distance and displayed more rearing than the males. In conclusion, oxycodone decreases anxiety-like behavior in rats, and oxycodone has a greater anxiolytic-like effect in males than females.